2019
DOI: 10.3390/ijms20061269
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Recombinant Wild Type Uricase from Indonesian Coelacanth (L. menadoensis) and Improvement of Its Thermostability by In Silico Rational Design and Disulphide Bridges Engineering

Abstract: The ideal therapeutic uricase (UOX) is expected to have the following properties; high expression level, high activity, high thermostability, high solubility and low immunogenicity. The latter property is believed to depend largely on sequence identity to the deduced human UOX (dH-UOX). Herein, we explored L. menadoensis uricase (LM-UOX) and found that it has 65% sequence identity to dH-UOX, 68% to the therapeutic chimeric porcine-baboon UOX (PBC) and 70% to the resurrected ancient mammal UOX. To study its bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…4 ). In attempt to further stabilize An96, we inserted disulfide bridges into the protein ( Craig and Dombkowski 2013 ; Yainoy et al 2019 ). One variant (Coel) had amino acid replacements at M25C and N287C, while a different variant (DbD3) had replacements at A223C and A130C.…”
Section: Resultsmentioning
confidence: 99%
“…4 ). In attempt to further stabilize An96, we inserted disulfide bridges into the protein ( Craig and Dombkowski 2013 ; Yainoy et al 2019 ). One variant (Coel) had amino acid replacements at M25C and N287C, while a different variant (DbD3) had replacements at A223C and A130C.…”
Section: Resultsmentioning
confidence: 99%
“…3A, supporting the hypothesis that H 2 O is the second nucleophile. We verified this finding using an H 2 18 O isotope-labeling assay, which directly verified H 2 O as the second nucleophile. The data showed that the m/z ratio of all characteristic 2-methylbutyric acid fragment ions containing hydroxyl groups increased by 2, compared with a control assay with normal H 2 16 O (Fig.…”
Section: Mechanism and Engineering Of Lovastatin Esterase Pcestmentioning
confidence: 55%
“…Our previous work showed that the main problems with PcEST are its poor soluble expression and thermostability (9). The highly flexible regions on protein surfaces sometimes affect the solubility of the proteins and/or reduce their thermostability (17,18), because they might enhance the entropy during protein unfolding by increasing the numbers of unfolded conformations (19). In the PcEST structure, the long loop in R2 and the antiparallel ␤-sheet that may participate in the conformation stabilization of R2 helix showed high flexibility with higher structural B factors.…”
Section: Structure-guided Engineering Of Pcestmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolation of uricase from green bean leaves [ [4]], Pseudomonas aeruginosa [ [5]], Streptomyces exfoliates UR10 from agricultural waste [ [6]], Bacillus subtilis strain SP6 [ [7]], Bacillus cereus SKIII [ [8]], Aspergillus welwitschiae strain 1-4 [ [9]]. Isolation of the uricase from the liver of rainbow fish, mackerel, trout, catfish, shark and tilapia [ [10]], Indonesian coelacanth [ [11]], camel liver [ [12]], and bovine kidney [ [13]]. Based on previous studies, this study will isolate and characterize the uricase from chicken (Gallus gallus domesticus) liver which are broiler and native chicken liver.…”
Section: Introductionmentioning
confidence: 99%